Vocabulary Mobile Learning Application in Blended English Language Learning - Polakova, Petra; Klimova, Blanka (Frontiers in Psychology, 2022)
Mobile devices and applications, which have become an integral part of our lives, are gradually used for different purposes, including learning languages in EFL classrooms. Since vocabulary plays an important role in the process of foreign language learning, the aim of this study was to explore the use of the vocabulary mobile learning application and its usefulness in blended English learning. Quantitative and qualitative approach to research was used, since the integration of both approaches created the possibility to solve complex research problem. The case study was based on the use of the developed mobile application called Angličtina Today the content of which corresponded to the language needs of the target group of students. The quantitative approach used a method of quasi-experiment aiming to achieve the pre-tests and post-test results of the students from the experimental and control groups. The results showed that the students facing blended learning, including mobile application in the process of language learning, achieved better results than the students exposed to the traditional, face-to-face education. In addition, the results revealed students´ overall satisfaction with the application. The main reasons for their satisfaction were improved vocabulary knowledge, ease of use, and enhanced motivation. Based on these findings from the current study, it can be argued that the vocabulary mobile learning application proved to be useful in the process of blended English language learning.